Pengaruh Iklim Organisasi KAMMI Terhadap Kampus - Muhammad Raditia Handika; Abdi Verdiansyaf; Maulana Andinata Dalimunthe (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research investigates the influence of the KAMMI organization's climate on the UINSU campus through a quantitative approach. The study aims to understand the impact of KAMMI's organizational climate on student perceptions and the overall academic environment at UINSU. The research delves into the background, formulates questions, and employs a cross-sectional design to gather data from a stratified random sample of UINSU students. The findings reveal a positive correlation between students' perceptions of KAMMI's organizational climate and their assessments of the campus environment. Active participation in KAMMI, collaborative programs, and effective communication emerge as crucial elements contributing to a positive organizational climate and tangible effects on campus life. The discussion interprets these results in the context of organizational climate theory, emphasizing the importance of alumni organizations in shaping student satisfaction and experiences. The implications of the study underscore practical recommendations for enhancing student engagement, developing collaborative programs, and improving communication channels. In conclusion, this research provides a comprehensive understanding of the dynamic between KAMMI's organizational climate and the UINSU campus environment. The study's recommendations offer practical insights for fostering a positive organizational climate, ultimately contributing to the continuous improvement of the campus experience for UINSU students.